The Effectiveness of Acupressure Combination of Temulawak in Increased Toddler Appetite: Efektifitas Akupresur Kombinasi Temulawak Dalam Peningkatan Nafsu Makan Balita - Faridah Hanum, Sri Mukhodim; Widowati, Hesty; Puspitasari; Filberta, Yusnita; Tjondro, Lidia Agustin (Universitas Muhammadiyah Sidoarjo, 2022)
Prolonged difficulty eating in children results in a decrease in the calorie intake needed so that it can affect the growth and development of children. Based on data from the Weighing Month in August 2020 in Java, it was found that the percentage of toddlers wasting was 8.0%. Acupressure and family medicinal plants, namely ginger, can be non-pharmacological therapy options to grow children's appetite. Acupressure is a form of energy stimulation by providing massage and stimulation at certain points on the body, while temulawak can increase appetite in patients with primary anorexia because temulawak contains curcumin which is able to correct abnormalities in bile, so that the process of absorption of food in the intestine is easier. good. The purpose of this study was to determine the effectiveness of acupressure combination of ginger in increasing the appetite of toddlers aged 1-5 years. The design used is a pre experimental design with a quantitative approach with a Wilcoxon pre and post test method. The variables in this study were acupressure and temulawak with appetite. The population in this study were children aged 1 to 5 years with a sample of 20 children Acupressure was performed 6 times (2 times a week) while ginger was given 1 time/day at a dose according to age and body weight for 3 weeks. The assessment was carried out twice before and after treatment with questionnaires and weight scales. Furthermore, the analysis of the two data was carried out with the Wilcoxon pre and post test. The results of this study indicate that there is a significant difference after treatment with a value of P = 0.000 (P<0.05), which means that there is an effect of acupressure and ginger on increasing toddlers' appetite based on weight gain.